Multiplex Immunofluorescence and Multispectral Imaging: Forming the Basis of a Clinical Test Platform for Immuno-Oncology - Hoyt, Clifford C. (Frontiers in Molecular Biosciences, 2021)
As immuno-oncology (I/O) emerges as an effective approach in the fight against cancer, multispectral imaging of multiplex immunofluorescence (mIF) is maturing as an analytical platform. The timing is fortuitous. Due to health economics considerations surrounding the use of I/O, there is an urgent need for tests that accurately predict response to the growing list of available therapies. Multispectral mIF provides several advantages over other biomarker modalities by enabling deeper interrogation of the intricate biology within the tumor microenvironment, including detection of cell-to-cell spatial interactions that correlate with clinical outcomes. It also provides a practical path for generating reliable and reproducible results in a clinically suitable, high-throughput workflow. In this chapter, we describe: 1.) Describe the principles behind multispectral mIF; 2.) Provide advice and recommendations on assay development and optimization, and highlight characteristics of a well-performing assay; and 3.) Discuss the requirements for translating this approach into clinical practice.